Design and Control of an Autonomous Robot for Mobility-Impaired Patients - Deb, Aarya; Wypych, Zachery; Lonner, Jess; Ashrafiuon, Hashem (IFAC-PapersOnLine, 2021)
A novel autonomous mobile robotic arm is designed and developed that can autonomously follow mobility impaired patients and prevent backwards and sideways falls. The robot is designed with differentially driven wheels and an arm with an end-effector to stop falls but otherwise will not contact the subject. A closed control algorithm is initially developed and simulated to ensure the robot will be able to follow any feasible trajectory. The control algorithm is then simplified, implemented, and tested on the robot using only a Lidar device for distance and orientation measurements and feedback. The mobile base in combination with a servomotor and simple switches, operating the end-effector, are shown to successfully prevent backward and sideway falls in preliminary tests.